De-Dollarization Trends in Southeast Asia: Assessing Indonesia's Monetary Sovereignty - Abdurokhim, Abdurokhim (Economics Monetary Journal, 2025)
Please be aware that in the past two decades, de-dollarization efforts in the Southeast Asian region, particularly Indonesia, have shown significant increases in response to global economic uncertainty and the dominance of the U.S. dollar. This study aims to analyze the trend of de-dollarization in Indonesia, evaluate its impact on monetary sovereignty, and formulate policy recommendations to strengthen Indonesia's position in the regional financial system. Using a qualitative descriptive approach with documentary analysis and secondary quantitative data from official institutions (Bank Indonesia, IMF, ADB, AMRO), this study explores the dynamics of the use of local currencies in bilateral transactions and the diversification of foreign exchange reserves. The results show a significant increase in transactions using the rupiah, especially through the Local Currency Settlement (LCS) framework with Malaysia and Thailand, which increased from 8% in 2017 to 18% in 2022. Additionally, the proportion of foreign exchange reserves held in non-dollar currencies increased, thereby strengthening exchange rate stability and enhancing national monetary policy flexibility. However, structural challenges such as limited financial infrastructure, foreign investor dominance, and economic openness still limit full monetary sovereignty. These findings emphasize the importance of regional policy synergy, strengthening the domestic real sector, and building an inclusive digital financial system. This study makes conceptual contributions to the dedollarization literature and offers strategic recommendations for policymakers to optimize Indonesia's monetary autonomy amid global dynamics.